2017
DOI: 10.24198/jsk.v2i4.12492
|View full text |Cite
|
Sign up to set email alerts
|

Survei Intervensi Ibu Hamil Kurang Energi Kronik (Kek) Di Kecamatan Jatinangor Tahun 2015

Abstract: Kurang Energi Kronik (KEK)  adalah kurangnya asupan energi berlangsung lama. Pada ibu hamil KEK merupakan keadaan ibu hamil menderita kekurangan energi yang berlangsung menahun sehingga menimbulkan gangguan kesehatan. Untuk mencegah gangguan kesehatan, faktor risiko serta komplikasi, maka dilakukan intervensi. Tujuan penelitian ini adalah melakukan survei intervensi pada ibu hamil KEK di Kecamatan Jatinangor tahun 2015. Metode penelitian menggunakan metode deskriptif dengan pendekatan cross-sectional. Diambil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
1
3
0
13
Order By: Relevance
“…In fact, nutrition assistance can directly affect pregnant women's behavior to consume nutritious food and thus positively increase the size of the middle-upper arm circumference on pregnant women with CED. This present study is in line with a study by Prawita et al (2017) that showed that all pregnant women with CED supported by food supplementation and health counseling had an increase in their body weight and MUAC. Likewise, a study by Silitonga (2018) also found that there is a significant association between nutritional counseling and body weight gain of pregnant women with CED.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, nutrition assistance can directly affect pregnant women's behavior to consume nutritious food and thus positively increase the size of the middle-upper arm circumference on pregnant women with CED. This present study is in line with a study by Prawita et al (2017) that showed that all pregnant women with CED supported by food supplementation and health counseling had an increase in their body weight and MUAC. Likewise, a study by Silitonga (2018) also found that there is a significant association between nutritional counseling and body weight gain of pregnant women with CED.…”
Section: Discussionsupporting
confidence: 93%
“…Chronic Energy Deficiency (CED) is a nutritional state which is characterized by a deficient energy intake for a period of several years (chronic), which results in some health problems (Prawita, indra Susanti, & Sari, 2017). Pregnant women are susceptible to CED and can damage both mother and infant's health and the quality of the baby.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Berdasarkan penelitian Arsy Prawita,dkk (2015), faktor-faktor yang mempengaruhi KEK antara lain: asupan makanan yang kurang, penyakit kronis, tingkat pendidikan, tinggi badan ibu, ibu tidak bekerja, posisi ibu dalam rumah tangga, lingkungan rumah di pedesaan, ibu hamil tidak dalam ikatan perkawinan, serta status ekonomi. 11 Sedangkan, menurut Abidah,dkk (2013) faktorfaktor yang berpengaruh terhadap kejadian anemia pada ibu hamil diantaranya yaitu pengetahuan, frekuensi Antenatal Care (ANC), status ekonomi dan status gizi. 12 Berdasarkan penelitian terebut, diketahui jika asupan energi, status gizi, dan frekuensi ANC berpengaruh terhadap kondisi ibu selama masa kehamilan.…”
Section: Pendahuluanunclassified
“…Salah satu penyebab tidak langsung tingginya AKI adalah status gizi ibu hamil yang buruk. Kekurangan gizi pada ibu hamil dan bayi telah menyumbang setidaknya 3,5 juta kematian setiap tahunnya dan memberikan konstribusi sebanyak 11% dari jumlah penyakit global di dunia (Prawita, Susanti, & Sari, 2017).…”
Section: Pendahuluanunclassified